Thomas Annan: photographer of Glasgow - Maddox, Amanda 1948-; Stevenson, Sara (The J. Paul Getty Museum, 2017)
"A survey of the life and publication history of the nineteenth-century Scottish photographer Thomas Annan"...Provided by publisher
"This publication accompanies the exhibition Thomas Annan: Photographer of Glasgow, on view at the J. Paul Getty Museum at the Getty Center, Los Angeles, from May 23 to August 13, 2017."...ECIP galley. - Includes index
Keywords: Annan, Thomas -- 1829-1887 -- Exhibitions; Annan, Thomas -- 1829-1887 -- Criticism and interpretation -- Exhibitions; Annan, Thomas -- 1829-1887 -- Bibliography -- Exhibitions; Annan, Thomas -- 1829-1887; Photography -- Scotland -- Glasgow -- Bibliography -- Exhibitions; Photographers -- Scotland -- Biography -- Exhibitions; Dokumentarfotografie; Fotografie; Landschaftsfotografie; Schottland; Glasgow; Ausstellungskatalog; Ausstellungskatalog -- J. Paul Getty Museum -- 23.05.2017-13.08.2017 -- Los Angeles, Calif.; Bibliografie; Biografie